Pengembangan Model Work Based Learning Kolaboratif (WBL-K) pada Pelaksanaan Magang di Politeknik Negeri Jakarta - Sarah Iasya; Sugiyarto Sugiyarto; Nina Sulistyowati (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The demographic bonus that will occur in Indonesia in 2045 is a challenge as well as an opportunity to immediately prepare competent human resources. The effort to prepare quality human resources is to link and match vocational education with the industrial world through the application of Collaborative Work Based Learning (WBL-K) in internships. The implementation of WBL-K aims to ensure that vocational education has a high level of efficiency and relevance to the needs of the industrial world. The purpose of this study is to determine the validity, practicality, and effectiveness of the application of the WBL-K model in the form of internships to improve the competence of polytechnic students. This research is an experimental research conducted at the Jakarta State Polytechnic. The instruments used in this study are in the form of pre-test and post-test questions. The data analysis used in this study is N-Gain and N-Gain difference test using the t-test to determine the practicality and effectiveness of the WBL-K model. Based on the results of the practicality and effectiveness test of the WBL-K model developed, it can be concluded that from the practicality and effectiveness test in the experimental class, the criteria are obtained that the WBL-K model is quite practical and effective in improving student competence.